Determinants of Skills Shortages and Hard-to-Fill Vacancies in the Hospitality Sector - Andrés J. Marchante; Bienvenido Ortega; Ricardo Pagán (European Regional Science Association (ERSA), 2005)
The aim of this paper is to analyse the regional determinants of hard-to-fill vacancies and skills shortages in the hospitality sector. The data source for this study was generated in the year 2000 and includes information on 181 hotels and 121 restaurants in Andalusia. The results of the estimations show that hourly net wages are the main instrument firms use to reduce hard-to-fill vacancies and skills shortages. However, there are several factors affecting the conditions of local labour markets — such as unemployment rates, the level of business activity, real estate prices and the location of the firm in relation to the main regional tourism destinations — that have a significant effect on the probability of having hard-to-fill vacancies and skills shortages.
Keywords: 330